ANALYTICAL METHOD VALIDATION OF GAS CHROMATOGRAPHIC METHOD FOR THE ESTIMATION OF RELATED SUBSTANCES IN TRIMETHYL ORTHO PROPIONATE . - DEVESHRI B. NARKHEDE; P. D. NARKHEDE; RAVINDRA R.P. (International Journal of Pharma and Bio Sciences, 2010)
A simple, precise, specific, accurate and reproducible Gas Chromatographic method has been developed for the estimation of related substances in Trimethyl Orthopropionate in bulk sample. A Chemito1000 system comprising with FID detector , Hamilton syringe , Chemito software was used to develop the method. The analyte was resolved by using carrier Nitrogen gas as mobile phase at the flow rate of 30ml/ min.The chemito GC1000 consisting of column 10%Carbowax(Chemito, 1/8” ID, 2meter L, particle size 80/100)at oven temp. 80ºC(2 min.)5ºC/ Min.150ºC; Injector temperature at 210ºC and the Detector temperature at 240ºC respectively. For Validation of Trimethyl OrthoPropionate the µl standard solutions of TMOP were applied at above set temperature programme. The chromatogram were developed with retention time at 2.987 with percent area at 99%.Then validation parameters like, Linearity (CorrelationCoefficient0.9947), Precision study (The determination of RSD,0.1089), Robustness(by changing parameters like temperature and flow rate does not affect the assay values , assay difference NMT 1%),Limit of Detection (at 0.5µl) etc. Were determined respectively. Analytical Method Validation Report for the Determination of Related Substances in Trimethyl OrthoPropionate for these valid parameters was prepared. Present study was undertaken with an objective of developing suitable, sensitive ,and simple analytical approach for estimation of organic impurities present in the API.